Physical Activity Levels, Sport Participation, and Exercise Outcomes in Individuals with Attention-Deficit/Hyperactivity Disorder: A Literature Review - Trzepizur, Paweł Arkadiusz; Samp, Nikola Agnieszka; Bekrycht, Beniamin Andrzej; Foryński, Jędrzej Marek; Stachurska, Michelle Martina; Zera, Kamila; Piekarska, Weronika; Radiczew, Konstancja; Rogala, Karolina; Wilczyński, Rafał (Quality in Sport, 2026)
Background. Attention deficit hyperactivity disorder (ADHD) affects approximately 7.2% of children and adolescents internationally and is associated with functional impairment across educational, social, occupational, and health behavioral domains. Despite evidence that physical activity benefits cognition and psychosocial functioning, participation remains markedly insufficient, with only 6.5% of adolescents with ADHD meeting all recommended movement guidelines. Aim. To synthesize evidence on physical activity levels, sport participation, exercise types, barriers and facilitators, sex differences, and dose effects in individuals with ADHD. Material and methods. PubMed search (January 2015 – May 2026); studies reporting physical activity, sport participation, or exercise outcomes in individuals with ADHD. Findings were synthesized narratively. Results. Several forms of physical activity — aerobic exercise, martial arts, racket sports, swimming, equine-assisted activities, target shooting, exergaming, combined aerobic-cognitive exercise, and multicomponent school-based programs — were associated with improvements in cognitive, behavioral, or psychosocial outcomes. Barriers were primarily related to executive dysfunction, motivational difficulties, and low self-esteem; facilitators were largely tied to direct experience of the benefits of exercise. Conclusions. Individuals with ADHD engage in physical activity at markedly insufficient levels and face distinctive barriers rooted in executive dysfunction and motivational dysregulation. Multiple forms of physical activity produced meaningful benefits, suggesting interventions need not be restricted to aerobic exercise alone. Sex-specific factors and exercise intensity warrant explicit consideration in intervention design.